232k views
1 vote
Given the function
h:x=px-(5)/(2) and the inverse function
h^(-1) :x=q+2x, where p and q are constants, find a) the value of p and q c)
h^(-1) h(-3)

User Alex Trott
by
6.4k points

1 Answer

6 votes

Answer:


p = (1)/(2)


q = 5


h^(-1)(h(3)) = 3

Explanation:

Given


h(x) = px - (5)/(2)


h^(-1)(x) = q + 2x

Solving for p and q

Replace h(x) with y in
h(x) = px - (5)/(2)


y = px - (5)/(2)

Swap the position of y and d


x = py - (5)/(2)

Make y the subject of formula


py = x + (5)/(2)

Divide through by p


y = (x)/(p) + (5)/(2p)

Now, we've solved for the inverse of h(x);

Replace y with
h^(-1)(x)


h^(-1)(x) = (x)/(p) + (5)/(2p)

Compare this with
h^(-1)(x) = q + 2x

We have that


(x)/(p) + (5)/(2p) = q + 2x

By direct comparison


(x)/(p) = 2x --- Equation 1


(5)/(2p) = q --- Equation 2

Solving equation 1


(x)/(p) = 2x

Divide both sides by x


(1)/(p) = 2

Take inverse of both sides


p = (1)/(2)

Substitute
p = (1)/(2) in equation 2


(5)/(2 * (1)/(2)) = q


(5)/(1) = q


5 = q


q = 5

Hence, the values of p and q are:
p = (1)/(2);
q = 5

Solving for
h^(-1)(h(3))

First, we'll solve for h(3) using
h(x) = px - (5)/(2)

Substitute
p = (1)/(2); and
x = 3


h(3) = (1)/(2) * 3 - (5)/(2)


h(3) = (3)/(2) - (5)/(2)


h(3) = (3 - 5)/(2)


h(3) = (-2)/(2)


h(3) = -1

So;
h^(-1)(h(3)) becomes


h^(-1)(-1)

Solving for
h^(-1)(-1) using
h^(-1)(x) = q + 2x

Substitute
q = 5 and
x = -1


h^(-1)(x) = q + 2x becomes


h^(-1)(-1) = 5 + 2 * -1


h^(-1)(-1) = 5 - 2


h^(-1)(-1) = 3

Hence;


h^(-1)(h(3)) = 3

User Richleland
by
6.3k points